Management building competitive advantage - Bateman, Thomas S.; Snell, Scott A. (Irwin/McGraw-Hill, 1999)
Although this revised edition of the text takes a traditional functional approach to management, it is organzied around four modern themes: cost, quality, speed and innovation.